Ecotoxicological assessment of PAHs using the freshwater planarian Girardia tigrina - Simão, Fátima Cristina Paulino (2020)
Freshwater planarians are animals that possess a set of features that has made them pivotal for research areas such as stem cell research, neurophar-macology, or ageing research. The appeal of these animals has stemmed from features such as the existence of adult stem cells distributed over their bodies, the presence of a simple brain sharing similarities with the vertebrate nervous system, or their apparent lack of ageing. The interest in freshwater planarians as experimental animals has spread to ecotoxicity testing, given features such as easy maintenance in laboratory setting, their sensitivity to environmental contaminants, and also the range of effects that can be evaluated in response to contaminants, such as teratogenicity, carcinogenicity, reproductive and be-havioural toxicity or neurotoxicity. Their predatory nature offers yet another interesting opportunity to include them in multi-species tests as epibenthic in-vertebrate predators. In the context of exploring the sensitivity of freshwater planarian endpoints to environmental contaminants, the present work used polycyclic aromatic hydrocarbons (PAHs) as model compounds. PAHs are ubiquitous contaminants in the environment, given the multitude of natural and anthropogenic sources and their ability to be transported over long distances through the air. As a major contaminant class in the environment, the risk as-sessment of PAHs has been challenging, given the array of metabolizing abili-ties among invertebrates, as well as the multitude of effects these compounds can elicit. For some invertebrate groups, such as freshwater planarians, there is virtually no (eco)toxicological information. With the ultimate goal of exploring freshwater planarians in the context of ecotoxicological research, this work used the freshwater Girardia tigrina as experimental animal and three PAHs with distinct number of aromatic rings, the 3-, 4- and 5-ringed phenanthrene, pyrene and benzo[a]pyrene, respectively. Several specific objectives were ad-dressed: development of novel planarian bioassays, evaluation of PAH toxicity potential accumulation in G. tigrina under different exposure scenarios. Along 6 experimental chapters, experimental protocols were refined and, more specifi-cally, a feeding protocol was developed in accordance with the specific features of G. tigrina. This freshwater planarian was also shown to be sensitive to PAHs, with mortality, disintegration of tissues, regeneration delays, behavioural impairments, biochemical changes, decreases in reproductive output and de-creased newborn fitness being observed: The severity of effects was well relat-ed with the concentration-dependent increase of PAH-type compounds in pla-narian tissues. However, despite chemical similarities, each PAH elicited differ-ent effects in planarians. The evaluation of feeding and locomotion in response to chemical stress was evidenced to be sensitive at short exposure periods, showcasing the potentialities of planarian behavioural endpoints for ecotoxicity testing. With longer exposure periods, fecundity was shown to be a sensitive endpoint, while increased behavioural anomalies in unexposed newborns re-sulting from B[a]P-exposed parents, evidenced the importance of newborn condition as a reproduction-related endpoint in planarians and for transgenera-tional studies. The evaluation of internal concentrations of PAH-type com-pounds in the head and tail portions of exposed planarians revealed that these compounds accumulated more in the heads of planarians, providing a hint on the potential neurotoxicity of these compounds, as suggested by the observed behavioural effects. Moreover, the accumulation of PAH-type compounds in G. tigrina exposed to B[a]P-contaminated sediments or to contaminated prey, evidenced their potential for ecotoxicological experiments with contaminated sediments and to evaluate trophic transfer of contaminants. The results ob-tained in the present work indicate that planarians are sensitive to chemical stress, with a multitude of available endpoints, while showing potential for in-clusion as invertebrate predators in multispecies studies as invertebrate preda-tors. Therefore, their usage for ecotoxicological research is strongly recom-mended.